Efficacy trial of Vi polysaccharide vaccine against typhoid fever in south-western China - Yang H.H.; Wu C.G.; Xie G.Z.; Gu Q.W.; Wang B.R.; Wang L.Y.; Wang H.F.; Ding Z.S.; Yang Y.; Tan W.S.; Wang W.Y.; Wang X.C.; et al. (Bulletin of the World Health Organization, 2001)
OBJECTIVE: To test the efficacy of locally produced Vi vaccine over a time period of longer than one year. METHODS: A double-blinded, randomized field trial was performed in Guangxi Zhuang Autonomous Region in south-western China, using 30 mg doses of locally produced Vi. Enrolled subjects were 3-50 years of age, although the majority (92%) were school-aged children, who have the highest rate of typhoid fever in this setting. A total of 131 271 people were systematically allocated a single dose of 30 mg of Vi polysaccharide or saline placebo. The study population was followed for 19 months, with passive surveillance conducted in the Ministry of Health and the Regional Health and Anti-epidemic Centre (HAEC). Clinically suspected cases of typhoid fever were confirmed by blood culture, or by serological reaction with O-antigen (Widal tests). FINDINGS: After 19 months, there were 23 culture-confirmed cases of typhoid fever in the placebo group versus 7 cases in the Vi group (Protective efficacy (PE) = 69%; 95% CI = 28%, 87%). Most of the isolates were from school-aged children: 22 cases in the placebo group versus 6 in the Vi group (PE = 72%; 95% CI = 32%, 82%). No serious post-injection reactions were observed. The locally produced Vi polysaccharide vaccine showed levels of protective efficacy similar to those for Vi vaccine produced in industrial countries. CONCLUSION: The slightly higher dose of vaccine did not seem to alter efficacy significantly in China.